2012
DOI: 10.1095/biolreprod.111.094482
|View full text |Cite
|
Sign up to set email alerts
|

A Decrease in DKK1, a WNT Inhibitor, Contributes to Placental Lipid Accumulation in an Obesity-Prone Rat Model1

Abstract: Placenta, as the sole transport mechanism between mother and fetus, links the maternal physical state and the immediate as well as lifelong outcomes of the offspring. The present study examined the consequences of maternal obesity on placental lipid accumulation and metabolism. Pregnant obesity-prone (OP) and obesity-resistant (OR) rat strains were fed a control diet throughout gestation. Placentas were collected on Gestational Day 21 for mRNA and oxidative stress analysis, and frozen placental sections were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 76 publications
3
45
1
Order By: Relevance
“…Here, we observed increased lipid content in the placentae from obese dams, consistent with findings in obese human placentae where it has been localized in the villi stroma and syncytium8. In our model as well as in obesity-prone rats, lipid was found to be localized predominantly in the decidua19. One study in Fatp2 and Fatp4 knockout mice20 observed an increased lipid deposition in the decidual/junctional zones of the placentae, suggesting these fatty acid transporters are essential for the trafficking of lipids across the placenta.…”
Section: Discussionsupporting
confidence: 90%
“…Here, we observed increased lipid content in the placentae from obese dams, consistent with findings in obese human placentae where it has been localized in the villi stroma and syncytium8. In our model as well as in obesity-prone rats, lipid was found to be localized predominantly in the decidua19. One study in Fatp2 and Fatp4 knockout mice20 observed an increased lipid deposition in the decidual/junctional zones of the placentae, suggesting these fatty acid transporters are essential for the trafficking of lipids across the placenta.…”
Section: Discussionsupporting
confidence: 90%
“…Total RNA isolation, cDNA synthesis and real-time PCR were performed as previously described (Strakovsky and Pan, 2011). A serial dilution was used to create a standard curve for quantification and a dissociation curve was analyzed following each reaction.…”
Section: Methodsmentioning
confidence: 99%
“…In the same model, FATP4 mRNA expression was shown to be downregulated by chronic exposure to IL-6, but without corresponding alteration in protein expression [81]. It has been reported in animal models of maternal obesity that placental mRNA expression of FATP1 and FATP4 are increased [130, 131]. …”
Section: Fatty Acidsmentioning
confidence: 99%